Broad ligament leiomyoma with cystic change mimicking as ovarian tumor - Kaur, Prabhdeep; Guha, Neena; Gupta, Parag; Sahu, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine leiomyomas are common benign gynaecological tumours, occurring in 20-40% of cases in India. Broad ligament fibroids, though rare (less than 1%), are the most frequent extrauterine site and can be mistaken for ovarian carcinoma due to their unusual location. This report presents a nearly asymptomatic 50-year-old woman with irregular menstrual cycles who was found to have a non-tender, mobile cystic mass equivalent to an 18-week gravid uterus. Ultrasound detected a 540 CC complex solid-cystic right adnexal lesion with an un-visualized ovary; CECT showed a 780 CC solid-cystic right ovarian mass, and MRI revealed a suspicious 570 CC solid-cystic lesion, raising concerns for malignancy. IVP was omitted as ureters were normal. Laparotomy identified a sizable cystic mass located on the right side within the broad ligament, which exhibited minimal resemblance to leiomyoma and resulted in mild anatomical distortion. Both the uterus and ovaries appeared unremarkable. Histopathological analysis confirmed the lesion as a broad ligament fibroid exhibiting extensive cystic degeneration. Due to this atypical presentation, immunohistochemical studies were recommended to exclude malignancy. Broad ligament leiomyomas, particularly those with solid and cystic components, may mimic ovarian malignancies during clinical and radiological assessment, complicating differential diagnosis due to their atypical presentation. Histopathology plays a crucial role in establishing a definitive diagnosis. This case is presented due to its infrequency and the diagnostic uncertainty it created for both clinicians and the patient.